An-Nadzâir Al-Mukhâdi’ah Baina Al-Lughah As-Sâsâkiyyah Wa Al-‘Arabiyyah Fî Qâmûs Al-Lughah As-Sâsâkiyyah Linâdzir Thair Wa Al-Istifâdah Minhâ Fî Ta’lîm Al-Lughah Al- ‘Arabiyyah Li As-Sâsâkiyyin Min Harfi M Ilâ Z - Eka Septiani Rahman; Fajar Siddiq (Mauriduna: Journal of Islamic Studies, 2021)
يهدف هذا البحث إلى اكتشاف النظائر المخادعة بين اللغة العربية والساساكية في قاموس اللغة الساساكية للكاتب ناظر طائر ومعرفة كيفية الاستفادة منها في تعليم اللغة العربية للساساكيين المبتدئيين تسهيلا لهم خلال تعلمهم اللغة العربية ولمساعدة المعلم في تعليم اللغة العربية. وانتهجت الباحثة المنهج الوصفي التحليلي في هذا البحث وهو المقارنة بين اللغة العربية والساساكية في قاموس اللغة الساساكية للكاتب ناظر طائر من حرف M إلى Z وتحليلها في اللغتين من حيث المعنى وطريقة النطق بالرجوع إلى بعض المعاجم العربية المعتمدة. وقد توصلت الباحثة إلى النتيجة وهي أن عدد الكلمات التي لها نظائر مخادعة بين اللغة العربية والساساكية في قاموس اللغة الساساكية من حرف M إلى Z بلغ حوالي 52 كلمة، ومن تلك الكلمات ما يتساوى في النطق ومنها ما يختلف اختلافا يسيرا كاختلاف المد، والتشديد، والحركة، والفونيم. وتكون الاستفادة من النظائر المخادعة عن طريق الحوار، والنص المقروء، والتدريبات اللغوية. The purpose of this study is to analyze the homonym between Arabic vocabulary and Sasak vocabulary in the Sasak Nazir Thair et al dictionary, as well as examples of teaching methods for Sasak beginner students who learn Arabic so that it makes it easier for them to learn Arabic and provide new innovations for Arabic language teachers.This research uses analytical descriptive method, which is a method that compares the Arabic and Sasak languages ​​in terms of meaning and pronunciation using the Sasak-Indonesian dictionary and some references from several Arabic dictionaries.The results of this study indicate that the number of homonyms in the Sasak-Indonesian dictionary reaches 52 sentences, and from these words have the same pronunciation and pronunciation with Arabic and others have slightly different pronunciation because of the vocal differences between the two languages. As for its application in teaching Arabic through conversation, text, and practice.